The ideal match; Views on marriage in Panji Paniba (1816) - Molen, Willem van der (Wacana, Journal of the Humanities of Indonesia, 2020)
Panji Paniba of 1816 is a Panji story. It is built on a plot which is characteristic of Panji stories: four Javanese kingdoms in a Hindu setting, a princess who disappears and a prince, her fiancé, who finds her again. Another characteristic of Panji tales is the happy ending of marriages and successions to thrones. Interestingly in Panji Paniba a foreign king has a role to play. Crucial to our understanding of this particular version of Panji stories is the special attention it pays to types of marriages. Three types can be distinguished: proper, improper but repairable, and objectionable. How these are defined and how they influence the development of the narrative is the topic discussed in the present article.